1995
DOI: 10.1172/jci117644
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the concentrations of magnesium and calcium in early porcine and rat wound fluids activate the cell migratory response.

Abstract: Accruing evidence indicates that the levels of extracellular Mg2+ and Ca2+ can have a distinct impact on the adhesive and migratory activities of many cell types. The physiological relevance of these observations, however, has remained largely unexplored. In the present study, wound fluids collected throughout the early stages of cutaneous wound repair were examined for possible Mg2" and Ca2+ fluctuations. Early in the process, when cell migration into the wound site is initiated, Mg2+ is elevated and Ca2+ is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 76 publications
9
79
0
Order By: Relevance
“…13 We have recently demonstrated that a 2 b 1 integrin-mediated pancreatic cancer cell adhesion to Type I collagen, an ECM protein shown to be highly upregulated in pancreatic cancer [14][15][16][17] and to promote the malignant phenotype in vitro and in vivo, [18][19][20][21][22][23][24][25] is promoted in 1.5 mM Mg 21 and inhibited in 1.5 mM Ca 21 , 21 and that the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen by affinity chromatography in 3 mM Mg 21 , can be eluted with 3 mM Ca. 2126 These data are consistent with our previous observations regarding the a 2 b 1 integrin, Type I collagen, and the various cell types involved in cutaneous wound repair, [27][28][29] of which strong parallels to the pancreatic cancer paradigm have been described. 30,31 During normal cutaneous wound healing in vivo, shifts in the concentrations of extracellular Mg 21 and Ca 21 have been shown to occur early in the process, activating the a 2 b 1 integrin-mediated migration of various wound healing cell types on Type I collagen, including epithelial keratinocytes.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…13 We have recently demonstrated that a 2 b 1 integrin-mediated pancreatic cancer cell adhesion to Type I collagen, an ECM protein shown to be highly upregulated in pancreatic cancer [14][15][16][17] and to promote the malignant phenotype in vitro and in vivo, [18][19][20][21][22][23][24][25] is promoted in 1.5 mM Mg 21 and inhibited in 1.5 mM Ca 21 , 21 and that the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen by affinity chromatography in 3 mM Mg 21 , can be eluted with 3 mM Ca. 2126 These data are consistent with our previous observations regarding the a 2 b 1 integrin, Type I collagen, and the various cell types involved in cutaneous wound repair, [27][28][29] of which strong parallels to the pancreatic cancer paradigm have been described. 30,31 During normal cutaneous wound healing in vivo, shifts in the concentrations of extracellular Mg 21 and Ca 21 have been shown to occur early in the process, activating the a 2 b 1 integrin-mediated migration of various wound healing cell types on Type I collagen, including epithelial keratinocytes.…”
supporting
confidence: 89%
“…The cell adhesion and reversibility data together with previous affinity chromatography and immunoprecipitation results demonstrating that Ca 21 can elute the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen-sepharose in Mg 2126 suggested that, as we have previously shown for fibroblasts, keratinocytes, endothelial cells and macrophages, [27][28][29] Ca 21 and Mg 21 could also be involved in the modulation of a 2 b 1 integrin-mediated pancreatic cancer cell migration on Type I collagen. We have previously demonstrated using anti-integrin function-blocking monoclonal antibodies in inhibition of cell migration assays, that the a 2 b 1 integrin specifically and exclusively mediates pancreatic cancer cell migration on Type I collagen, with no involvement from the a 1 b 1 integrin.…”
Section: Casupporting
confidence: 69%
See 3 more Smart Citations